A life cycle assessment of the ISIS-II neutron and muon source - Wakeling, H (JACoW Publishing, 2024)
The ISIS-II Neutron and Muon source is the proposed next generation of, and successor to, the ISIS Neutron and Muon Source based at the Rutherford Appleton Laboratory in the United Kingdom. Anticipated to start construction in 2031, the ISIS-II project presents a unique opportunity to incorporate environmental sustainability practices from its inception. A Life Cycle Assessment (LCA) will examine the environmental impacts associated with each of the ISIS-II design options across the stages of the ISIS-II lifecycle, encompassing construction, operation, and eventual decommissioning. This proactive approach will assess all potential areas of environmental impact and seek to identify strategies for minimizing and mitigating negative impacts, wherever feasible. This presentation will provide insights into the process and first results of the LCA of the entirety of the ISIS-II project.